Literatur Review: Pengaruh ROA, ROE dan EPS Terhadap Harga Saham pada Perusahaan Perbankan yang Terdaftar di BEI - Saputra, Muh.Hendra Dwi; Ananda.T, Sheika; Nurshabrina; Hasriyana (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
The capital market is one alternative that can influence companies to meet their funding needs. Banking services come first in developing the country's economy. With the existence of a capital market, it will be easier for companies to obtain funds so that economic activities in various sectors can be increased. The aim of this research is to determine the influence of Roa, Roe, and Eps on share prices in banking companies listed on the Indonesian Stock Exchange. This research uses descriptive analysis of the data obtained. The design used in this research is a literature review or literature study. Literature review is a search and research of the literature by reading and reviewing various journals. In general, the results of this study show that EPS is the variable that most consistently has a positive and significant effect on stock prices, both partially and simultaneously. Meanwhile, the influence of ROA and ROE on stock prices varies depending on the sector and research method. Simultaneous analysis indicates that these three variables often have a significant influence on stock prices, although the partial results are not always consistent.